Social learning in practice: A review of lessons, impacts and tools for climate change - Harvey, Blane; Ensor, Jonathan; Garside, Ben; Woodend, John; Naess, Lars Otto; Carlile, Liz (2013)
The aim of this report is to provide a detailed review of documented social learning processes for climate change and natural resource management as described in peer-reviewed literature. Particular focus is on identifying (1) lessons and principles, (2) tools and approaches, (3) evaluation of social learning, as well as (4) concrete examples of impacts that social learning has contributed to. This paper has sought to contribute to reflections on the role that social learning might play and the impacts it might have in supporting decision making on climate change, agriculture and food security. Understanding social learning is important if we wish to respond effectively to increasingly complex and “wicked” problems such as climate change; to break down barriers between producers and users of research, and increase the capacity of organisations to learn. This study, conducted on behalf of the Climate Change Agriculture and Food Security (CCAFS) program of the CGIAR, offers a range of framings and evidence of successful social learning approaches. It reflects on how this evidence relates to the existing change areas already being pursued by the CCAFS programme and on the gaps that are revealed through an analysis of a bounded set of literature.